2014
DOI: 10.1016/j.amjcard.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality Risk in Individuals With Atrial or Ventricular Premature Complexes (Results from the Third National Health and Nutrition Examination Survey)

Abstract: Premature ectopic beats are frequently detected on routine 12-lead screening-electrocardiogram (ECG). However, their prognostic importance in individuals without known cardiovascular disease (CVD) is not well established. We evaluated prognostic value of atrial premature complexes (APC’s) and ventricular premature complexes (VPC’s) detected by a single 12-lead-ECG. A prospective cohort of 7504 participants selected from nationally-representative, community-dwelling individuals living in United States, enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…The database search identified 325 potentially eligible studies. After screening titles/abstracts and retrieving full‐text articles, a total of 11 studies including 129 514 participants fulfilled the inclusion criteria, 2 of which were from the same study: Atherosclerosis Risk in Communities (ARIC; see Supporting Information, Figure 1, in the online version of this article) …”
Section: Resultsmentioning
confidence: 99%
“…The database search identified 325 potentially eligible studies. After screening titles/abstracts and retrieving full‐text articles, a total of 11 studies including 129 514 participants fulfilled the inclusion criteria, 2 of which were from the same study: Atherosclerosis Risk in Communities (ARIC; see Supporting Information, Figure 1, in the online version of this article) …”
Section: Resultsmentioning
confidence: 99%
“…Atrial premature complexes might be a sign of a subclinical CVD or an early marker of structural and electrical remodeling in response to training. 27,28 Two studies found an increased risk of SCD, 28,29 , whereas Cheriyath et al 30 found no increased risk of SCD. There are only sparse data dealing with APCs during exercise.…”
Section: Discussionmentioning
confidence: 96%
“…Lin et al 5 reviewed 24 h Holter tracings of 3351 individuals with apparently normal heart and concluded that multiform PVCs were associated with a significant higher HR for mortality, hospitalisation, transient ischaemic attacks and new-onset heart failure and new-onset atrial fibrillation in the following 10 years. On the contrary, study by Qureshi et al 6 in an 18-year follow-up of 7504 patients with arrhythmias from standard 12-lead ECGs showed increased mortality and morbidity with premature atrial complexes and not PVCs. One meta-analysis study suggested that the poor prognosis of PVCs maybe confounded by occult structural heart diseases in those so-called ‘normal’ patients which are not divulged by advanced cardiac tests 7.…”
Section: Introductionmentioning
confidence: 84%